1990
DOI: 10.1056/nejm199002083220603
|View full text |Cite
|
Sign up to set email alerts
|

Intrafamilial Clustering ofHelicobacter pyloriInfection

Abstract: Colonization of the gastric antrum by Helicobacter pylori (formerly Campylobacter pylori) has been associated with primary gastritis. We determined the frequency of colonization by H. pylori in gastric-antrum biopsy specimens from 93 children undergoing gastroscopy for the evaluation of upper gastrointestinal symptoms. We also determined H. pylori IgG antibody levels by enzyme-linked immunosorbent assay in coded serum samples from these children, family members, and control subjects of comparable ages. Among 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
267
2
10

Year Published

1991
1991
2005
2005

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 541 publications
(288 citation statements)
references
References 29 publications
9
267
2
10
Order By: Relevance
“…27) Studies to date have also indicated that H. pylori, in common with nearly all infections, is established during childhood, 8) is more frequent in developing countries than in industrialized countries, 28) is inversely proportional to socioeconomic level, 6) and shows a high rate of intra-familial infection. 29) As Japan has no significant variations in ethnicity, and there is no apparent class system, the focus of our study has been how sanitation and living conditions during childhood might have affected H. pylori infection. Thus, the questionnaire content was predicated on the subject's living conditions at age 10 and was designed to address issues of drinking water, availability of flush toilets, residential area, family size, nursing and birth order.…”
Section: Discussionmentioning
confidence: 99%
“…27) Studies to date have also indicated that H. pylori, in common with nearly all infections, is established during childhood, 8) is more frequent in developing countries than in industrialized countries, 28) is inversely proportional to socioeconomic level, 6) and shows a high rate of intra-familial infection. 29) As Japan has no significant variations in ethnicity, and there is no apparent class system, the focus of our study has been how sanitation and living conditions during childhood might have affected H. pylori infection. Thus, the questionnaire content was predicated on the subject's living conditions at age 10 and was designed to address issues of drinking water, availability of flush toilets, residential area, family size, nursing and birth order.…”
Section: Discussionmentioning
confidence: 99%
“…8,27,30,78,94 Rothenbacher et al 119 estudaram a prevalência do H. pylori em 1.143 crianças e seus respectivos acompanhantes (n=1.074) mediante teste respiratório com C 13 -uréia. Os autores concluíram que pais infectados, especialmente as mães, podem desempenhar importante papel na transmissão do H. pylori entre familiares, à semelhança do que se observa em relação a outras bactérias da cavidade oral, como é o caso do Streptococcus mutans.…”
Section: Unidade Familiarunclassified
“…pylori are highly genetically diverse, providing Ϸ1,400 informative sites within 4.5 kb of sequence, and their global genetic structure parallels that of humans (28). Moreover, epidemiological studies have shown that transmission occurs predominantly within families (29)(30)(31)(32). This point is critical because vertical transmission is more likely to reflect human migrations than is the horizontal transmission that is typical of many microbes.…”
mentioning
confidence: 99%